Malay micro-entrepreneurs and state’s regulatory role: A case of Penang - Omar, Muhamad Fuzi; Zulkifli, Khairul Syakirin; Mohd. Adnan, Normala; Jamaiuddin, Norhaslinda; Abdul Hamid, Rohana (2016)
The micro-entrepreneurs groups are always being associated with the Malays businessmen. This group, however, are important for the development of the country towards achieving the status of developed nation by 2020. Concurring with this, this study aims to explain the regulatory role, as a factor, that contributes to the progress of the Malay’s entrepreneurs’ business. This factor is being established based on the factor analysis findings from a survey conducted in Penang. A total of 300 questionnaires were obtained from different groups of Malay entrepreneurs. The finding shows that the regulatory factor, which include the proper information, facilities dissemination, safety, transformation system, rules on ethnic relation are crucial for the micro-entrepreneurs to help progress their business.